ANALISIS MISKONSEPSI SISWA PADA MATERI TRIGONOMETRI MENGGUNAKAN METODE CERTAINTY OF RESPONSE INDEX TERMODIFIKASI DI SMA - Muhammad Dwiki Annadzili; Halini Halini; Dede Suratman (UNIVERSITAS TANJUNGPURA, 2022)
The research purpose is to analyze the misconceptions by using the certainty of response index modified in trigonometric equations at class XI State Senior High School 9 Pontianak. that Research method used in this research was a case study. The subjects in this research were seven students of class XI IPA 1 and IPA 2 of State Senior High School 9 Pontianak. The instruments used in this research were diagnostic tests and interview guidelines. From the result of the study, obtained 8 out of 32 students had computation misconceptions, 9 out of 32 students had generalized misconceptions, 1 out of 32 students had specialization misconceptions, and 1 out of 32 students had theoretical misconceptions. Misconceptions experienced are caused by students are students' associative thinking, incomplete reasoning, wrong intuition, stages of student cognitive development, and student abilities. Generalizing misconceptions are the most common misconceptions experienced by students, the cause of this misconception is wrong intuition and the stage of students' cognitive development.